The dual systems model-impulsivity and narcissism as the reflexive system and self-regulation as the reflective system-of smartphone addiction - Tan, Kit-Aun; Nik Jaafar, Nik Ruzyanei; Bahar, Norharlina; Ibrahim, Normala; Baharudin, Azlin; Wan Ismail, Wan Salwina; Abdul Aziz, Melisa; Sim, Su Tein (Mary Ann Liebert, 2024)
The exploration of underlying mechanisms leading to the development of smartphone addiction has been limited, with only a few studies incorporating theories to provide explanations. Drawing upon the Dual Systems Model, this study tested the hypothesis that the reflective system of self-regulation would mediate the relation between the reflexive system of impulsivity and narcissism, and smartphone addiction in a sample of 298 undergraduate students. Participants completed a self-administrated web-based questionnaire containing measures of impulsivity (the Barratt Impulsiveness Scale), narcissism (the Narcissistic Personality Inventory), self-regulation (the Self-Regulation Scale), and smartphone addiction (the Smartphone Addiction Inventory). The findings from structural equation modeling revealed that self-regulation served as a significant mediator between impulsivity and smartphone addiction, as well as between narcissism and smartphone addiction. These findings offer insights that can contribute to the development of interventions and strategies that target impulsivity and narcissism by enhancing self-regulation skills.